Absenteeism of Some Students in Secondary School in Sokoto East, Nigeria - Yusuf Yahaya Miya; Yusuf Sarkingobir; Abbas Abubakar Hiliya; Abdullahi Sanusi Sidi; Zayyanu Bello (Journal of Elementary and Secondary School, 2023)
Education is a right to every child, but Sokoto is suffering from many issues ravaging education, therewith, children/ adult abandoning school/ class is one of the sufferings of education in the area. The objective of this study is to evaluate the school/ class absenteeism in school in Sokoto East, Nigeria. The demographic characteristics of respondents shows that; all the respondents are Muslims, Hausa/ Fulani, and males (100.0%). The education was degree (33.7%), Students (50.0%), and lastly higher national diploma (16.7%). The types/ forms of school/ classes absenteeism been shown by the students of the observed school in Sokoto East, Nigeria. The most submitted form was, Students sitting outside classes during class hours (33.3%), and others are: “Some classes were closed (25.0%)” and “Students abandoning classes before the closing time (25.0%)”. The last was students completely refusing to come to schools sometime (16.7%). The submitted reasons behind students absenteeism in school in Sokoto East, Nigeria are as follows: Poor supervision of students by teachers (24.0%), Poor supervision of teachers’ by leaders (18.0%), Insecurity (17.7%), Poor supervision by communities (15.0%), Poor management by administration (12.0%), Lack of enough teachers (8.0%), and corruption (5.3%). Therein, the effects of absenteeism are as follows: Poor education/ academic performance (42.0%), Inability to go to higher education (30.0%), and School dropout (28.0%). The possible solutions suggested by the respondents on how to tackle the issues of students abstaining schools or classes. The most submitted solution was “Proper monitoring of school by administration (36.7%)” then “Proper monitoring by teachers (27.3%)”, then “Proper parental monitoring (22.7%)”, and the last submitted response was “Proper monitoring of school by community (13.3%)”. There exists school and class absenteeism, and have the tendency to affect education and in turn development of the area and state at large. Proper monitoring of schools, students, and teachers are needed from the side of government, community, and school heads.